Social networks and the creation of the Pitt Rivers Museum - Larson, F; Petch, A; Zeitlyn, D (SAGE Publications, 2007)
We consider how far different `networks of connection' have structured the relationships between curators, collectors and objects at the Pitt Rivers Museum at Oxford University. Museum collections are generated through complicated, fluctuating circulations of people and things that are literally endless and, when there is a high standard of computerized documentation, network analysis can be a stimulating and revealing methodological tool. Network analysis can reveal patterns in sets of social relationships that are too large to process or analyse mentally, and it can be a spur to more in-depth, nuanced research. An introduction to network theory and a consideration of `network' as a metaphor for social and material interactions more broadly is followed by a discussion of our research into the history of the Pitt Rivers Museum and an assessment of the strengths and weaknesses of network analysis as a research tool in the museum context.